Influence of rift geometry over successive post-rift sedimentation: Tectonostratigraphy of the eastern Kopeh Dagh Belt (NE Iran). (August 2022) - Aghababaei, Abdullah; Adollahie-Fard, Iraj; Caçador Martins-Ferreira, Marco Antonio; Ghaemi, Farzin; Rahimi, Behnam; Moussavi-Harami, Reza
Abstract: Well, seismic (2D and 3D) and AHe age data, complemented by field surveys, were analyzed with the objective of investigating the tectono-stratigraphic evolution of syn- and post-rift sedimentary basins in the eastern Kopeh Dagh Belt (NE Iran), a region well known for its important oil and gas occurrences. The study was focused on evaluating how and when the geometry of syn-rift structures influenced the development of the post-rift sedimentation. Our results show that the Middle Jurassic rifting stage influenced the geometry of the post-rift basins. Carbonate buildup of the Upper Jurassic (Mozduran reservoir) was formed in the low relief accommodation zones between the Middle Jurassic opposing half-grabens in parallel to the sedimentation of argillaceous carbonates within the adjacent troughs. This geometry was also transmitted to the Lower Cretaceous, affecting the deposition of a relevant siliciclastic system (Shurijeh reservoir). The role of rifting was crucial in the distribution of reservoir facies and the generation of the structural-stratigraphic traps in the study area, which were also affected by late tectonic inversion. Uplift and denudation is likely to have occurred up to Late Miocene. Highlights: Outlining the rift basins geometry of the study area in the form of opposing half-grabens based on the 2D and 3D seismic data. Detection of the three rift initial, development and termination systems tracts of the rift basin. Highlighting influences of the variable-grained syn-rift sediments on the differential compaction across the study area. Presenting the low relief accommodation zone between the two opposing half-grabens as a potential platform environment for deposition of a porous carbonate gas-bearing reservoir.